Socio-Demographic Factors Shaping Parental Awareness of Children’s Positive Self-Concept Development - Bustamam, Nurbaity; Asfaruddin, Khairiah; Yahya, Martunis; Chalidaziah, Wan (Universitas Negeri Padang, 2025)
Parents play a crucial role in shaping a child’s self-concept, although socio-demographic factors may affect awareness of this responsibility. A total of 326 parents (93 fathers and 233 mothers), aged between 19 and 82 years, from various districts in Aceh participated in the study. They completed the Parental Awareness Scale of Self-Concept Promotion (PAS-SCP), a 42-item self-report instrument developed by the authors. The scale assesses three dimensions of parental awareness in promoting children’s positive self-concept: cognitive, affective, and behavioural. Content validity was confirmed through expert review, and reliability testing showed acceptable internal consistency (Cronbach’s α = .79–.86). Data were analysed using bivariate correlations (point-biserial and Spearman’s rho) and mean comparisons with effect sizes. Results indicated that parental education (r = .56, p < .01, large effect) and occupational field (r = .41, p < .01, moderate effect) were positively correlated with awareness. Conversely, age showed a negative correlation (r = –.29, p < .05, small-to-moderate effect). Gender differences were minimal (d = 0.05). These findings emphasise the importance of parental education and occupational background in fostering self-concept awareness. The results offer practical guidance for school counsellors and policymakers to enhance family-based interventions.